Loss of protein C vs protein S results in discrepant thrombotic phenotypes - Chia-Jui Ku; Xinge Yu; Queena Y. Zhao; Steven J. Grzegorski; Jeffrey G. Daniel; Allison C. Ferguson; Jordan A. Shavit (Blood Advances)
Abstract: Venous thrombosis is a leading cause of morbidity/mortality and associated with deficiencies of the anticoagulant protein C (PC; PROC) and its cofactor, protein S (PS; PROS1). Heterozygous mutations increase the risk of adult-onset thrombosis, whereas homozygous mutations result in pre/neonatal lethal thrombosis. Phenotypes of patients with PC and PS deficiency are generally considered clinically indistinguishable. Here, we generate proc (zebrafish PROC ortholog) and pros1 knockouts through genome editing in zebrafish and uncover partially discordant phenotypes. proc−/− mutants exhibited ∼70% lethality at 1 year of age, whereas pros1−/− survival was unaffected. Induced venous endothelial injury in both mutants revealed reduced occlusive thrombus formation. This is consistent with the consumptive coagulopathy of zebrafish antithrombin 3 knockouts, which also results in spontaneous venous thrombosis. However, proc and pros1 mutants revealed a discrepancy. Although both mutants demonstrated spontaneous thrombosis, proc−/− was localized to the cardiac and venous systems, whereas pros1−/− was intracardiac. Aside from coagulation, PC has been shown to have PS-independent roles in inflammation. proc mutants displayed altered inflammatory markers and defects in neutrophil migration independent of pros1. Transcriptomic analysis and gene knockdown identified novel proc genetic interactions with adgrf7, a G protein-coupled receptor (GPCR) not previously known to be involved in coagulation. In summary, our data reveal differences between PC- and PS-deficient thrombosis, with cardiovascular tissue–specific phenotypes and survival differences, suggesting the possibility of underlying clinical differences in affected patients. This model of complete proc−/− deficiency in an accessible organism will facilitate further in vivo study of these distinctions, as well as PS-dependent and -independent functions of PC.